2018
DOI: 10.3892/ol.2018.9206
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal changes in the quantity and function of osteoblasts cultured in�vitro in patients with myelodysplastic syndrome

Abstract: Changes in bone marrow niches can lead to the occurrence of myelodysplastic syndrome (MDS). As an important part of the bone marrow niche, osteoblasts serve a key role in the progression of MDS. The present study investigated the quantity and function of osteoblasts and, through in vitro assays, detected changes in signaling pathways and the association with progression in MDS patients. The ratios of osteoprogenitors (CD34+OCN+) and OCN+CD34−Lin− osteoblasts in MDS patients were significantly less than those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…This may be due to the gradient porous structure allowing more tissue ingrowth and blood vessels that result in a cooperative angiogenesis mechanism of CD34 and VEGF along with Ocn at week 8 and vWF at week 4 that increased the speed of new bone regeneration through the nutrient and oxygen flow improvement [70] in comparison to smaller pore sizes. This is in accordance with the studies of Gao and Bolander who demonstrated that the Ocn + CD34+ cell population displayed more mature osteoblasts and mineralized matrix tissue in vitro [71,72] which is due to the paracrine effect of CD34 + cells that causes the secretion of VEGF and their synergistic angiogenesis/ osteogenesis signals on bone regeneration [73].…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the gradient porous structure allowing more tissue ingrowth and blood vessels that result in a cooperative angiogenesis mechanism of CD34 and VEGF along with Ocn at week 8 and vWF at week 4 that increased the speed of new bone regeneration through the nutrient and oxygen flow improvement [70] in comparison to smaller pore sizes. This is in accordance with the studies of Gao and Bolander who demonstrated that the Ocn + CD34+ cell population displayed more mature osteoblasts and mineralized matrix tissue in vitro [71,72] which is due to the paracrine effect of CD34 + cells that causes the secretion of VEGF and their synergistic angiogenesis/ osteogenesis signals on bone regeneration [73].…”
Section: Discussionsupporting
confidence: 92%